1996
DOI: 10.1021/ja9609718
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of 6α-(Hydroxymethyl)penicillanate Complexed to the TEM-1 β-Lactamase from Escherichia coli:  Evidence on the Mechanism of Action of a Novel Inhibitor Designed by a Computer-Aided Process

Abstract: The crystal structure of the complex of the TEM-1 β-lactamase from Escherichia coli inhibited by 6R-(hydroxymethyl)penicillanic acid (1) is reported herein. This is the first structure for an acyl-enzyme intermediate with a substrate reported for a native class A β-lactamase. This compound was designed and synthesized as a molecule that would acylate the active site of the enzyme, but would resist deacylation by virtue of the fact that its C 6R hydroxymethyl moiety was expected to occupy the space near the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
127
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 15 publications
10
127
0
2
Order By: Relevance
“…Incidentally, the 6␣HMP rotamer seen in chains A, C, and D of OXA-58 is similar to that seen in 6␣HMP bound to TEM-1 (PDB code 1TEM) (see Fig. S3 in the supplemental material) (33). In the TEM-1-6␣HMP complex, it was noted that the hydroxyl group of 6␣HMP displaced the structurally conserved deacylating water molecule, and that hydrogen bonding with Glu-166 may prevent the glutamate from activating an incoming water molecule.…”
Section: Resultsmentioning
confidence: 56%
“…Incidentally, the 6␣HMP rotamer seen in chains A, C, and D of OXA-58 is similar to that seen in 6␣HMP bound to TEM-1 (PDB code 1TEM) (see Fig. S3 in the supplemental material) (33). In the TEM-1-6␣HMP complex, it was noted that the hydroxyl group of 6␣HMP displaced the structurally conserved deacylating water molecule, and that hydrogen bonding with Glu-166 may prevent the glutamate from activating an incoming water molecule.…”
Section: Resultsmentioning
confidence: 56%
“…The position of this water molecule is crystallographically conserved (31,36,41) unlike in class D enzymes (42)(43)(44). Perturbation of the hydrogen bonding network of this water molecule or the physical displacements of the water molecule by the steric bulk of the C-6 side chains of a ␤-lactam are possible mechanisms to render the ␤-lactamase deacylation-deficient (20,(45)(46)(47). This is the goal in designing new generations of ␤-lactams that are stable toward ␤-lactamases (47).…”
Section: Mechanism Of ␤-Lactammentioning
confidence: 99%
“…39,40) Several structural studies on the acylenzyme intermediate analogues indicated that Ser130 made a hydrogen bond with the carboxyl group. 7,[41][42][43] From these experimental findings, the function of Ser130 was thought to be binding a substrate. Díaz et al suggested that Ser130 did not only take part in substrate binding but also enzymatic catalysis.…”
Section: Deacylation Mechanism Of Class a B-lacta-masementioning
confidence: 99%